Inter-Rater and Intra-Rater Reliability of the Kansas University Sitting Balance Scale - Franc, Ingrid A.; Mauldin, Samantha; Roberts, Magdalena; Rosa-DiStefano, Gregoria (Occupational therapy in health care, 2023)
Kluding et al., created The Kansas University Sitting and Standing Balance Scales (KUSSBS) in 2006 to meet the need for objective documentation of balance and for a tool without a floor effect. Rater reliabilities were established by Kluding for the standing scale, but not for the sitting balance scale (KUSitBS). The aim of this study was to establish inter- and intra-rater reliability for the KUSitBS. Four occupational therapists were recruited to rate a videotaped performance of a simulated patient. Resulting inter-rater reliability inter-class coefficients (ICC) are good, ICC = .877, p < .01, suggesting that sitting balance on the KUSitBS was rated similarly across coders. Intra-rater reliability ICC are excellent, ICC = .914, indicating that each occupational therapist rated sitting balance on the KUSitBS similarly at initial assessment and then again two weeks later. In order to have confidence in using any assessment tool, intra- and inter-rater reliability must be established. This study's results advance the use of the KUSitBS with adult populations.